VARIASI DIAMETER NOSEL DAN KETINGGIAN PENYIRAMAN MENGGUNAKAN IRIGASI CURAH (SPRINKLER IRRIGATION) TERHADAP PEMADATAN TANAH - Marien A Gultom; Hilda Agustina; R. Mursidi Mursidi (Jurnal Teknik Pertanian Sriwijaya, 2012)
The objective of this research was to find out the best combination of nozzle diameter and height of watering of the soil compaction by considering of irrigation spraying efficiency which is best to be determined to value Coefficient of Uniformity and Distribution of Uniformity. This research was done by applying the water to irrigation area in time needed to each treatment in order to soil compaction. The research used description method followed by tabulation and graphical presentations with two factors (A and B) and two replications. Factor A was the nozzle diameter (1 mm, 2 mm, 3 mm) and factor B was the height of watering (1 m, 1½ m, 2 m). The observed data were include water content (%), bulk density (g/cm3), soil compaction (%), coefficient of uniformity (%) and distribution of uniformity (%). The result showed that the highest value of water content was 69.66% (D3T1) which is the treatment with combination of nozzle diameter by 3 mm and height of watering by 1 m and the lowest of water content was 46.20% (D1T3) which is the treatment with combination of nozzle diameter by 1 mm and height of watering by 2 m. The treatment with combination of nozzle diameter 3 mm and height of watering by 2 m (D3T3), was the best treatment with bulk density 1.338 g/cm3, porosity 31,53%, the soil compaction 26.001%, coefficient of uniformity 80.51%, distribution of uniformity 74.14%. In reality, combination between of nozzle diameter and height of water did not have a value of Uniformity Coefficient (?85%) and Uniformity Distribution (?75%).Keywords: Nozzle, Sprinkler irrigation, Soil compaction, Uniformity Coefficient , Uniformity Distribution